Spatial variability of sediment oxygen consumption and benthic nutrient fluxes in the continental shelf of the Southern Yellow Sea during spring - Baek, Ju-Wook; Kim, Sung-Han; Kim, Kyung-Tae; Choi, Jin Young; Jeong, Hyun-Jeong; Lee, Chang Hwa; An, Sung-Uk; Lee, Jae Seong (Frontiers in Marine Science, 2025)
To understand the factors controlling organic carbon (OC) and nutrient cycling in continental shelf sediments, we estimated total sediment oxygen uptake (TOU) and benthic nutrient flux (BNF) in the Southern Yellow Sea (SYS) during spring. The OC (0.28 to 1.58%), TN (0.03 to 0.22%), C/N ratio (7 to 11), and δ13C (–23.81 to –22.23‰) in the surface sediments showed spatial variation. The TOU ranged from 11.9 ± 0.02 to 20.5 ± 0.03 mmol O2 m−2 d−1, depending on the spatial distribution of OC content, with higher values in finer sediments. Sediment OC oxidation rates varied between 9.1 and 15.8 mmol C m−2 d−1, accounting for 5−87% of primary production in surface waters. The BNFs were comparable with other continental shelves, with dissolved inorganic nitrogen and dissolved inorganic phosphate fluxes contributing 1 to 33% and 2 to 14%, respectively, of the nutrients required for primary production. The findings suggest that sediment OC quantity and quality, influenced by sediment type, are major factors controlling the spatial variation of benthic OC cycles in the SYS. However, the benthic-pelagic coupling in the SYS during spring was weak, primarily because of low sediment OC oxidation and BNF rates. This study highlights the need for further research on temporal variability to fully understand the biogeochemical cycles in the Yellow Sea.